Comparative Effectiveness of National Sports Funding Policies: A Data-Driven Analysis in Recent Years - Yi Qing Xie (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This paper conducts a comparative analysis of national sports funding policies in the United States, China, and Russia over recent years. By adopting a data-driven approach, the study evaluates how each country allocates and administers funding to sports and assesses the effectiveness of these strategies in promoting sports development. Unlike the existing literature on art funding modes, this research specifically targets the sports sector, identifying unique funding characteristics and outcomes in each nation. The analysis reveals that, although all three countries prioritize sports funding, their methods and impacts vary significantly due to differences in governmental involvement, cultural emphasis on sports, and the operational mechanisms of funding distribution. This study provides a detailed discussion on the comparative merits and drawbacks of the sports funding policies in these countries, offering insights into how governmental departments enhance or hinder sports development through their funding strategies. The findings aim to contribute to the broader understanding of global sports policy effectiveness, guiding policymakers seeking to refine sports funding models to achieve better athletic and societal outcomes.